Cattaneo-Christov heat and mass flux effect on upper-convected Maxwell nanofluid with gyrotactic motile microorganisms over a porous sheet. (August 2022) - Waqas, Hassan; Farooq, Umar; Hussain, Mohib; Alanazi, Abdullah K.; Brahmia, Ameni; Hammouch, Zakia; Abo-Dief, Hala M.; Safaei, Mohammad Reza
Highlights: 2-D UCM fluid flow with Cattaneo-Christov heat and mass flux, motile microorganisms, and bioconvection across a porous sheet studied. Brownian motion, thermophoresis effects, thermal radiation, and activation energy are considered. The microbiological field is reduced when the bioconvection Lewis number increases. For the more excellent buoyancy ratio value, the velocity field is decreased. The thermal field of species is reduced for a more significant Prandtl number. Abstract: The bioconvection nanofluid flow study is one of the most popular topics since it has a wide variety of physical significance in biofuels, bioengineering, and medicinal research. The current study aims to investigate the features of two-dimensional UCM fluid (upper-convected Maxwell nanofluid) flow with Cattaneo-Christov heat and mass flux, motile microorganisms, and bioconvection across a porous sheet. The model incorporates Brownian motion and thermophoresis effects, as well as thermal radiation and activation energy. A proper similarity transformation transforms the governing system of partial differential equations into acceptable ODEs. We used the built-in numerical approach bvp4c in the commercial program MATLAB for the mathematical integration of the generated non-linear issue. The behavior of important physical factors is visually examined. The importance of engineering factors such as local Nusselt number, local Sherwood number, and local density number of microorganisms is also revealed. The stretching parameter increased the velocity field, but the magnetic parameter had the reverse effect. The velocity field is decreased for the increasing values of slip parameter and power-law index. The thermal field is increased for the higher variations of Biot number and temperature ratio parameter. Furthermore, species' thermal and solutal fields are lowered for more significant fluctuations in thermal and solutal relaxation parameters. The microbiological field is reduced when the bioconvection Lewis number increases.